Competitive Biological Activities of Chitosan and Its Derivatives: Antimicrobial, Antioxidant, Anticancer, and Anti-Inflammatory Activities - Suyeon Kim (International Journal of Polymer Science)
Chitosan is obtained from alkaline deacetylation of chitin, and acetamide groups are transformed into primary amino groups during the deacetylation. The diverse biological activities of chitosan and its derivatives are extensively studied that allows to widening the application fields in various sectors especially in biomedical science. The biological properties of chitosan are strongly depending on the solubility in water and other solvents. Deacetylation degree (DDA) and molecular weight (MW) are the most decisive parameters on the bioactivities since the primary amino groups are the key functional groups of chitosan where permits to interact with other molecules. Higher DDA and lower MW of chitosan and chitosan derivatives demonstrated higher antimicrobial, antioxidant, and anticancer capacities. Therefore, the chitosan oligosaccharides (COS) with a low polymerization degree are receiving a great attention in medical and pharmaceutical applications as they have higher water solubility and lower viscosity than chitosan. In this review articles, the antimicrobial, antioxidant, anticancer, anti-inflammatory activities of chitosan and its derivatives are highlighted. The influences of physicochemical parameters of chitosan like DDA and MW on bioactivities are also described.